2016
DOI: 10.1016/j.ypmed.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with leisure time physical activity among ELSA-Brasil participants: Ecological model

Abstract: The main objective of the study was identify the prevalence and factors associated with leisure time physical activity (LTPA) in adult participants of the Longitudinal Study of Adult Health (ELSA-Brasil). The LTPA was measured using the International Physical Activity Questionnaire (IPAQ), long version. A hierarchical ecological model was built with the possible factors associated with LTPA distributed across blocks. We estimated crude and adjusted odds ratios (ORs) and 95% confidence intervals (95% CIs) using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
1
14
1
4
Order By: Relevance
“…In ELSA-Brasil, this association was observed with respect to practising recreational physical activity. 36 The results of this study confirm that retirement status and age independently lead to improvements in lifestyle. Possibly, advancing age induces a greater awareness of the importance of promoting health and preventing disease for those who want to be active and healthy as they grow older.…”
Section: Discussionsupporting
confidence: 74%
“…In ELSA-Brasil, this association was observed with respect to practising recreational physical activity. 36 The results of this study confirm that retirement status and age independently lead to improvements in lifestyle. Possibly, advancing age induces a greater awareness of the importance of promoting health and preventing disease for those who want to be active and healthy as they grow older.…”
Section: Discussionsupporting
confidence: 74%
“…The prevalence of SB among participants of the ELSA-Brasil, 23.7% in men and 22.7% in women were minor than those observed in studies conducted in Germany 19 , 36.1% in men and 24.5% in women. In addition it was observed that men spend more sitting time at the weekend (10.4%) than women (6.7%), although they do more leisure-time physical 13 thatis, it is possible that the sitting time that the women do not have at the weekend is due to the inadequate division of tasks at the domestic level that overloads them. It is noteworthy that in the study conducted in Germany SB was considered with the cutoff point> 6 hours of sitting time.…”
Section: Discussionmentioning
confidence: 99%
“…The schooling was classified in incomplete elementar, complete elementar, high-school and college. The weekly consumption of beer was classified in " < 1500 ml" = 0 or "≥ 1500 ml" = 1; and the current smoking was classified in "no" = 0 and "yes" = 1 SB was the dependent variable, while the independent variables were grouped into blocks from an adapted theoretical ecological model 13,18 : the social demographic environment (age and level of education); the behavioral environment (leisure time physical activity, commuting physical activity, beer consumption, current smoking); and biological environment (overweight, obesity and abdominal obesity).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations